Instructions matter: Individual differences in navigation strategy and ability. - Boone, Alexander P.; Maghen, Bryan; Hegarty, Mary (Memory & Cognition, 2019)
Individual differences in navigation strategy in the dual-solution paradigm (DSP) indicate that some people prefer to take learned routes, while others prefer to take shortcuts (Boone, Gong, & Hegarty, Memory & Cognition, 46, 909–922, 2018; Marchette, Bakker, & Shelton, Journal of Neuroscience, 31, 15264–15268, 2011). Although work using the DSP has highlighted biases toward certain navigation strategies within individuals, a question remains as to why navigators do show a bias. Here, we questioned whether a bias toward navigation by learned routes indicates inability to take shortcuts, or whether other factors are at play, such as task demands and preferences. In two experiments, we began to untangle the association between the ability to construct survey knowledge, which is necessary if one is to take shortcuts (i.e., competence), and navigation strategy (i.e., performance) in virtual-reality navigation. Participants learned a route through a virtual environment and then navigated to goal locations in two experimental sessions. In Experiment 1, each participant navigated under two different instructions ("go to the goal" vs. "take the shortest path to the goal"), whereas in Experiment 2 two groups navigated under the same instructions in both sessions. Converging results from these experiments indicated that participants used more shortcuts overall under the shortcut instructions, and that this was not attributable to additional task exposure. Men were more likely to take shortcuts, under both the standard and shortcut instructions. This work indicates that the use of learned routes in the DSP does not necessarily imply that a person cannot take a shortcut, highlighting a dissociation between strategy and ability.